(3EVGAI GdCOehS hQjGVI GdTehS ef CMcGe UGMH GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi Lejd UfjYg CeG HYO aEfg bO hUd di HMeO Gddg hSejJg ZVGAI GdCOehS hQjGVI GdTehS s
(3BNQgG (B:s
(3hGTedg HTGed jefg haVdg Gddge CZaQ dfG hCQMefG hhGdOjfG ef Ydjg jG CQMe GdQGMejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(505 d) s
Keywords: (3GdeLGejYs